Rapid and label-free detection of Aflatoxin-B1 via microfluidic electrochemical biosensor based on manganese (III) oxide (Mn3O4) synthesized by co-precipitation route at room temperature. (9th July 2022) - Singh, Avinash Kumar; Dhiman, Tarun Kumar; Lakshmi, G B V S; Raj, Rishi; Jha, Sandeep Kumar; Solanki, Pratima R
Abstract: Aflatoxin B1 (AFB1) is the most toxic mycotoxin, naturally occurring in food items, and it causes several types of lethal diseases. Therefore, a rapid and convenient detection method for AFB1 is the first step toward overcoming the effect of AFB1. The current work presents the development of an efficient microfluidic electrochemical-based biosensor using tri-manganese tetroxide nanoparticles (Mn3 O4 nps) for AFB1 detection. The Mn3 O4 nps were synthesized at room temperature through the co-precipitation route. Its phase purity, structural and morphological studies have been characterized through x-ray diffraction, Raman spectroscopy, energy-dispersive x-ray, Fourier transform infrared spectroscopy and transmission electron microscopy. The mask-less UV-lithography was carried out to fabricate the three-electrode chip and microfluidic channel of the microfluidic electrochemical biosensing system. The designed microfluidic immunosensor (BSA/Ab-AFB1/Mn3 O4 /ITO) was fabricated using the three-electrode chip, microfluidic channel in poly-dimethyl siloxane. The fabricated sensor exhibited the 3.4 μ A ml ng −1 cm −2 sensitivity and had the lowest lower detection limit of 0.295 pg ml −1 with the detection range of 1 pg ml −1 to 300 ng ml −1 . Additionally, the spiked study was also performed with this immunoelectrode and a recovery rate was obtained of 108.2%.